Vibration Isolation of Asymmetric Rigid Plate Using One and Pair Pre-bent Strut at Each Corner under Static and Dynamic Axial Excitation - Ali Elkafrawy; Anwar Kandil; Moustafa Helaly; Abu-Bakr Omar (Port Said Engineering Research Journal, 2012)
This paper is concerned with the influence of vibration isolators in the form of post-buckled elastic clamped-clamped one and pair strut to relief the vibrating machines from the harmful effects of vibration. These vibrations are in most cases uncontrollable and lead to sudden failure, therefore, mechanical engineers in preventive maintenance sections have to control, isolate, and minimize the harmful effects of such unwanted vibrations. A mathematical model consists of pre-bent post-buckled one and pair strut acting as vibration isolators supporting an asymmetric rigid plate. The model is subject to axial harmonic excitation at the base, and allowed to displace laterally with respect to axial center line of the isolated plate. The displacement transmissibility is calculated over a wide range of frequencies and plotted in form of design charts. The transmissibility plots are used to recognize the ranges of frequencies, at which isolation can be maintained. The resonance frequencies of the system can be easily depicted from the design graphs. The present study reveals that at resonance frequencies the most effective transmissibility is well below unity. Vibration characteristics are determined under specific frequencies such that the physical behavior of the system can be thoroughly analyzed. All variables used in the analysis are normalized, such that the results aren‟t dependent on any material or geometric property. In this way, the obtained results can be applied over a wide range of elastic materials, regardless of the type of material or section properties.